Pengaruh Media Gambar Seri Terhadap Kemampuan Menulis Teks Prosedur Siswa Kelas VII SMP Negeri 30 Muaro Jambi - Atika, Mitarijuni; Rasdawita, Rasdawita; Rahmawati, Rahmawati (Universitas Negeri Padang, 2024)
AbstractThe aim of the research was to determine the effect of using serial image media on the ability to write procedural texts for class VII students at SMP Negeri 30 Muaro Jambi. This research was carried out from January 16 2024 to January 29 2024. The sampling technique used random sampling technique. Data collection techniques use tests, documentation and observation. In this research the tests carried out were pre-test and post-test. The data analysis technique in this research is very important to determine learning outcomes in the learning process using series image media. Before analyzing data, things that need to be considered are testing the prerequisites for data analysis and hypothesis testing. The research results show that the use of serial image media in procedural text writing skills has a significant influence in improving students' abilities in writing procedural texts.Keywords: Series Images, Writing Procedure Text